Steric Oscillations of the Baltic Sea Level - Zakharchuk Eugenii; Sukhachev Vladimir; Tihonova Natal'ya Aleksandrovna; Litina Ekaterina Nikolaevna (Russian Journal of Earth Sciences, 2023)
The main purpose of the paper is to estimate the capabilities of NEMO 3.6 regional reanalysis data for a realistic description of the Baltic Sea steric level oscillations, the spatio-temporal structure research and causes of modern sea level changes, induced by fluctuations in water density, in the range of interannual and seasonal variability scales. Comparison of the steric level oscillations series calculated from contact measurements of temperature and salinity at oceanographic stations and from regional reanalysis data is carried out by evaluating various statistical accuracy criteria. The paper shows that the reanalysis data allow reproducing the Baltic Sea steric level oscillations quite accurately. Estimates of linear trends indicate that in the period 1993–2020 in the open Baltic and in the west of the Gulf of Finland, the steric sea level is mainly decreasing, while in the Gulf of Bothnia the steric level is increasing. Harmonic analysis of steric level oscillations showed that the annual harmonic 𝑆a in the range of seasonal variability makes a predominant contribution to steric level oscillations, its amplitude significantly exceeds the amplitudes of the harmonics 𝑆sa, 𝑆ta and 𝑆qa. The thermosteric component has the main influence on seasonal steric level oscillations, and only in the south-west of the sea there is a significant influence of the halosteric component. During the period under review, positive linear trends were observed in the amplitudes changes of the harmonics 𝑆a, 𝑆sa, 𝑆ta and 𝑆qa in most regions of the Baltic Sea, however, in the south-west of the open Baltic, a decrease in the amplitudes of all four harmonics of seasonal steric level oscillations was observed in the south-west part of the Open Baltic Sea. In conclusion, based on the obtained results, it is assumed that the identified modern regional changes in the Baltic Sea steric level oscillations are associated with an increase in air temperature, an increase in precipitation, a decrease in wind intensity, a desalination of the upper quasi-homogeneous layer and an increase in deep and near-bottom waters salinity caused by water exchange with salty waters of the North Sea.